2018
DOI: 10.1021/acscatal.8b03011
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed [5+2]- and [5+1]-Annulations between Ynamides and 1,2-Benzisoxazoles with Ligand-Controlled Chemoselectivity

Abstract: This work describes two distinct annulations between ynamides and 1,2-benzisoxazoles with chemoselectivity controlled by ligands. With IPrAuCl/AgNTf2, aryl-substituted ynamides undergo [5+2]-annulation reactions, whereas P­(t-Bu)2(o-biphenyl)­AuCl/AgNTf2 alters the chemoselectivity of the same ynamides to implement [5+1]-annulation reactions. 13C-Labeling experiments confirm that a 1,2-sulfonamide shift is involved in the [5+1]-annulation process. A plausible mechanism is postulated to rationalize the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…Generally, the subsequent reactions tend to occur at the carbene center via nucleophilic attack (type a ), or 1,2‐C−C bond migration (type b ) (Scheme 1B). As our continuous interests in the development of the new strategies for the synthesis of heterocycles, we recently found that 1,4,2‐dioxazoles, [12a] 4,5‐dihydro‐1,2,4‐oxadiazoles, [12b] benzo[ d ]iso‐xazoles, [12c,d] benzofurazans [12e] and benzofurazans N ‐oxides [12e] (see Scheme 1A) could also be used as efficient nitrene transfer reagents [12,13] to promote gold‐catalyzed cycloaddition reactions with ynamides. During our studies on ynones, [14] we envisioned that α‐keto, α’‐imino gold carbenes I would be generated from ynones.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the subsequent reactions tend to occur at the carbene center via nucleophilic attack (type a ), or 1,2‐C−C bond migration (type b ) (Scheme 1B). As our continuous interests in the development of the new strategies for the synthesis of heterocycles, we recently found that 1,4,2‐dioxazoles, [12a] 4,5‐dihydro‐1,2,4‐oxadiazoles, [12b] benzo[ d ]iso‐xazoles, [12c,d] benzofurazans [12e] and benzofurazans N ‐oxides [12e] (see Scheme 1A) could also be used as efficient nitrene transfer reagents [12,13] to promote gold‐catalyzed cycloaddition reactions with ynamides. During our studies on ynones, [14] we envisioned that α‐keto, α’‐imino gold carbenes I would be generated from ynones.…”
Section: Methodsmentioning
confidence: 99%
“…[86] The reaction displayed a distinct ligand-controlled chemoselectivity, where P(t-Bu) 2 (o-biphenyl)AuCl/AgNTf 2 preferred the [5 + 1]-annulation pathway. [85] With P(t-Bu) 2 (obiphenyl)AuCl/AgNTf 2 catalytic system, the aryl-substituted ynamides preferred a [5 + 1]-annulation pathway to produce six-membered azacycles as the major product in a mixture of Zand E-isomers, with a minor amount of [5 + 2]-annulation product. The mechanism of the [5 + 1]-annulation reaction involves a 1,2-sulfonamide shift as confirmed by 13 C-labeling experiments (Scheme 63).…”
Section: [5 + 2] Annulationmentioning
confidence: 99%
“…In 2018, the groups of R. S. Liu [85] and Y. Liu [86] independently reported highly chemoselective, ligand-controlled, Au(I)-catalyzed [5 + 1] and [5 + 2]-annulations between ynamides and 1,2benzisoxazoles (Scheme 66).…”
Section: [5 + 1] Annulationmentioning
confidence: 99%
“…The intramolecular cyclization of 2‐alkynylaryl azides 1 is a well‐established process that would generate the α‐imino gold carbene intermediate A , which can be further captured by a variety of internal/external nucleophiles. On the other hand, anthranil 2 , [1a,4] 1,2‐benzisoxazole 3 [5b,c] and related nitrene transfer reagents are known to add to the alkynes, leading to the α‐imino gold carbene intermediates B . We speculated that the reaction of 2‐alkynylaryl azide 1 in the presence of anthranil 2 or 1,2‐benzisoxazole 3 should lead to different products, depending on the intra vs intermolecular nitrene transfer process, regioselectivity and the α‐imino gold carbene intermediate involved.…”
Section: Introductionmentioning
confidence: 99%